Subcutaneous granuloma caused by Kodamaea ohmeri in an immunocompromised patient in China. (27th December 2019) - Yu, Qian; Yan, Jianna; Gao, Zhiqin; Yang, Hong; Tang, Yichen; Yang, Lianjuan
Abstract: We present a case of subcutaneous granuloma caused by Kodamaea ohmeri and describe the histopathological characteristics and skin lesions caused by this pathogen . A 55‐year‐old woman, with a history of rheumatoid arthritis, presented with red, painless plaque on her forehead, persistent for 3 months; based on the histopathological and mycological findings and gene sequencing, the patient was diagnosed with subcutaneous granuloma caused by K. ohmeri . This report highlights that early identification and diagnosis and optimal regimens are vital in the management of this intractable infection.